DISTRIBUTION AND SOURCES OF PERSISTENT ORGANOCHLORINE PESTICIDES IN SEAWATER AND SEDIMENTS IN TRANSITIONAL SEASON FROM BANTEN BAY - Dede Falahudin; Khozanah Munawir (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Studies on distribution of organochlorine pesticides in water column and sediments from Banten Bay were conducted during transitional season on April and October, 2001. The objectives of the study were to determine the concentration and distribution of total organochlorine pesticides in water column and sediments in transitional seasons, and to identify its sources. Our study showed the concentration of pesticides organochlorine in water column ranged between 0.366 and 4.391 ng/l with an average of 1.952 ng/l in April (location 1), and 0.357 and 2.998 ng/l with an average of 1.203 ng/l in October (location 2). And then pesticide concentration in sediment were ranged between 0.263 and 2.090 µg/l dry weight (dw) with an average of 1.281 µg/l in June (location 1), and 0.068 to 10.095 µg/l dw with an average of 1.775 µg/l in October (location 2). The result indicated different influence of the season on organochlorine pesticides concentration and there was fresh input of DDT in the study area.